Endogenous peace processes and the resolution of Afu-Afughi religio-cultural conflict in Nanka, Southeastern Nigeria (2011)
This study looks at a communal conflict, termed 'afu- afughi ’religio-cultural conflict in Nanka, southeastern Nigeria, and the efforts made at resolving it, including the employment of endogenous peace processes. It is discovered that while the western-oriented peace approach achieved minimal results, endogenous peace processes were employed. The paper concludes that cultural meanings which the people could identify with are associated with the home-grown peace approach, and this ‘native understanding’ contributed to its acceptability, thereby affirming the continued relevance of endogenous peace model in contemporary Igbo society